Effect of H2O and its-resulting groups on coal-nitrogen evolution and transition in the initial stage of oxy-steam combustion - Shuang YUE; Haohao DING; Shuo ZHAO; Yue ZHANG; Dikun HONG; Haishun DENG (Meitan xuebao)
The 3th generation oxy-rich combustion technology, that is oxy-steam combustion with O2 and H2O as working medium, has recently attracted much attention due to its great potential and stability in the field of CO2 capture. Given that the effect of H2O on coal ignition and combustion is complex and non-linear, it is still unclear about the effect of H2O on coal-nitrogen evolution, particularly in high H2O concentration. In this case, the traditional low-nitrogen combustion technology would not be suitable for O2/H2O combustion, increasing the risk of excessive nitrogen oxide (NOx) emissions. In this paper, the migration and transition of organic nitrogen during coal devolatilization in O2/H2O combustion has been studied by using the ReaxFF molecular dynamic (MD) simulation and combining atomic labeling method, emphasizing on the migration route of nitrogen-containing functional groups and the formation of nitrogen-containing precursor. This will help to develop the technology of low-nitrogen combustion for the oxy-steam combustion. Results show that in the initial stage of coal devolatilization, the presence of high H2O concentration greatly promotes the formation of hydroxyl group (e.g. OH radical and C—OH group). It is beneficial to break aromatic ring and to release nitrogen-containing precursors, but it is not obvious in the initial stage of coal devolatilization. The formation of a large number of hydroxyl groups promotes the conversion of quaternary nitrogen (N-Q) in the aromatic ring to pyridine nitrogen (N-6) at the carbon boundary. In the meanwhile, the migration of N-6 and pyrrole nitrogen (N-5) to oxidized/amorphous nitrogen (N-X) is intensified. In the initial stage of coal devolatilization, the solid products obtained at high humidity have higher contents of N-6 and N-X, a lower stability of nitrogen-containing functional groups in coal, as well as a higher activity of reactivity sites. As time goes on, the presence of H2O and its resulting groups change the source of nitrogen-containing precursors. The conversion rates of N-6 to HCN and N-5 to NH3 are increased, but have little influence on the yields of HCN and NH3.